The role of men in recurrent miscarriage; a Narrative Review - Abedi, Amir Reza; Rahavian, Amir; Shariatpanahi, Samira; Aliakbari, Fereshte (Archives of Men's Health, 2020)
Background and Method: Recurrent Pregnancy Loss (RPL) is defined as the occurrence of two or more consecutive miscarriages within the first 20 weeks of pregnancy. The key challenge remains to be what it is that has to be done with couples experiencing RPL. Infections, endocrine disturbances, a suboptimal uterine environment, advanced maternal age, and genetic influences are some of the factors which may increase the chances of RPL occurrence. Despite all medical and research efforts, approximately 40 percent of RPL cases are categorized as unexplained. This is while amongst all the various factors which may lead to such condition, fathers’ genetic influences have often been ignored in the past. In fact, parental chromosomal anomalies, gene mutations such as the microdeletion of chromosome Y, and/or some polymorphism of HLA-G have shown to contribute and lead to miscarriage. Result: Furthermore, high levels of Reactive Oxygen Species (ROS) can cause DNA damage in spermatozoa. Meantime, sperm DNA damage has been closely linked with indicators such as fertilization, embryo quality, implantation, spontaneous abortion, congenital malformations, and childhood diseases. Sperm Chromatin Structure Assay (SCSA) is a test to measure DNA fragmentation. Moreover, the other SCSA parameter that needs to be considered is high DNA stainability (HDS). It is worth mentioning that HDS is associated with frequency of aneuploidy in spermatozoa. In addition, high HDS can be associated with an increased risk of early abortion in IVF and ICSI cycles. Conclusion: Additionally, increasing paternal age and varicocele can increase the risk of miscarriage. Advanced Paternal Age (APA) can also increase the relative risk of offspring neurocognitive defects. In saying that, the microsurgical varicocelectomy effectively increases the odds of natural pregnancy, the rate of high-quality embryos, and the success rate of in vitro fertilization.